Afforestation in Cold Arid Zones of Himachal Pradesh Problems and Solutions - Banerjee, U. K. (Indian Forester, 1993)
The paper deals with the problems of afforestation in the cold arid areas of Himachal Pradesh some work has been done previously to afforest these areas. But choice of wrong species along with poor moisture retaining capacity of the soil are the main reasons of failure. In order to afforest these areas choice of proper species and improvement in the irrigation technique will have to be kept in view.